2012
DOI: 10.2478/v10130-012-0002-y
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Farm Size on Gendered Involvement in Crop Cultivation and Decision-making Responsibility of Moldovan Farmers

Abstract: This research describes the influence that farm size has on gendered involvement in crop cultivation and decision making about what crops to grow where, irrigation and marketing among small and medium-sized farmers in Moldova. Findings reveal that overall crop cultivation is characterized by gendered patterns that vary according to farm size. Overall men have much more input into decision making than do women but women on small farms have more input in decisions than do the women on medium-sized farms. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…For example, in Georgia, the share of agriculture in rural employment was 58.3 percent, which is very high compared to other countries of the transition region (FAO 2014). indicate that about 75.4 percent of women considered vegetable cultivation as their primary responsibility whereas 65.7 percent of men viewed the substantially higher-value-added vineyard cultivation as such (Grigsby et al 2012). In a related finding, the results of a 2013 agricultural survey in Georgia indicated that 1.5 percent of men in rural areas were engaged in agricultural processing activities compared to only 0.6 percent of women (Pellillo et al 2014).…”
Section: Rural Development and Agriculturementioning
confidence: 99%
“…For example, in Georgia, the share of agriculture in rural employment was 58.3 percent, which is very high compared to other countries of the transition region (FAO 2014). indicate that about 75.4 percent of women considered vegetable cultivation as their primary responsibility whereas 65.7 percent of men viewed the substantially higher-value-added vineyard cultivation as such (Grigsby et al 2012). In a related finding, the results of a 2013 agricultural survey in Georgia indicated that 1.5 percent of men in rural areas were engaged in agricultural processing activities compared to only 0.6 percent of women (Pellillo et al 2014).…”
Section: Rural Development and Agriculturementioning
confidence: 99%
“…Traditionally, male labor in these countries is associated with cultivation and harvesting whereas women's work often comprises “helper” tasks, including taking care of children, keeping the account books, and providing medical insurance and additional income with off‐farm work (e.g., Brandth ; Sachs ). More recently, however, some researchers have found evidence to suggest that gendered roles are more complex, depending on what a farm produces (Grigsby, Español, and O'Brien ; Machum ). There is also some evidence of movement from a traditional patriarchal toward more of a partnership model in some sectors of Western agriculture (Beach ).…”
Section: Introductionmentioning
confidence: 99%